Signifikansi Nauru dalam Kebijakan Bantuan Finansial Australia (2001-2008) - Bramantyo Tri Asmoro (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2016)
Australia has foreign aid policy distributed to Asia Pacific region annually. Specifically for South Pacific region, Melanesian countries such as Papua New Guinea, Solomon Islands, Fiji and Vanuatu had always been main priorities. But since 2001, Australia increased its financial aid to Nauru, a small country located in Micronesia. Compared to other countries in South Pacific, Australia's financial aid to Nauru tends to increase. This fact raise a question about why Australia increased its financial aid to Nauru, especially since 2001? To answer the question, the writer use foreign aid motivation theory, regional security, and Australia's defence concept, continental defence. The result of this research is, Australia increased its financial aid to Nauru because Australia want to maintain regional security. Nauru is potential failed state that can disturbed regional security in South Pacific.